Virus-Specific T Cells for the Treatment of Systemic Infections Following Allogeneic Hematopoietic Cell and Solid Organ Transplantation - Abby Green; Jeremy D. Rubinstein; Michael Grimley; Thomas Pfeiffer (2024)
Abstract Viral infections are a major source of morbidity and mortality in the context of immune deficiency and immunosuppression following allogeneic hematopoietic cell (allo-HCT) and solid organ transplantation (SOT). The pharmacological treatment of viral infections is challenging and often complicated by limited efficacy, the development of resistance, and intolerable side effects. A promising strategy to rapidly restore antiviral immunity is the adoptive transfer of virus-specific T cells (VST). This therapy involves the isolation and ex vivo expansion or direct selection of antigen-specific T cells from healthy seropositive donors, followed by infusion into the patient. This article provides a practical guide to VST therapy by reviewing manufacturing techniques, donor selection, and treatment indications. The safety and efficacy data of VSTs gathered in clinical trials over nearly 30 years is summarized. Current challenges and limitations are discussed, as well as opportunities for further research and development.